AKTIVITAS ANTIBAKTERI ISOLAT BAKTERI ENDOFIT TANAMAN KUNYIT (Curcuma longa L.) TERHADAP PERTUMBUHAN Staphylococcus aureus - Saskya Maulidya Astari; Ambar Rialita; Mahyarudin Mahyarudin (Jurnal Fitofarmaka Indonesia, 2021)
Staphylococcus aureus is a commensal bacterial  of the body that can become pathogen at any time. Along with the increase of antibacterial resistant cases, it is necessary to explore the new potential metabolites as antibacterial. Endophytic bacteria that live on turmeric (Curcuma longa L.) are thought to be able to produce secondary metabolites that are similar and even more varied than their host plants.To determine the antibacterial effect of secondary metabolite compounds of turmeric (Curcuma longa L.) endophytic bacteria on Staphylococcus aureus. Endophytic bacterial isolates were subcultured on NA media with a streak plate method. Antibacterial activity test useds disk diffusion method. Potential endophytic bacterial isolates were characterized based on colony morphology, cell morphology and biochemical properties and secondary metabolite compounds produced are identified with a ciulei method. A total of 17 endophytic bacterial isolates were successfully subcultured. All endophytic bacterial isolates had antibacterial activity range from 7.4-13.76 mm. One of the most potential isolates was M8 isolate which had similarity with a genus Pseudomonas. The secondary metabolites that was produced bt M8 isolates were alkaloids, terpenoids and saponins. The most potential endophytic bacteria as antibacterial belong to the genus Pseudomonas and had alkaloids, terpenoids and saponins.